Unprotected lands: A case study of a wildland-urban interface community in "No-Man's land". (15th March 2023) - Billings, Mark; Carroll, Matthew; Paveglio, Travis
Abstract: There are areas of the United States that have no formalized fire protection. These lands are colloquially referred to as "no-man's land" but are recognized by many land management agencies as unprotected lands. Unprotected lands are generally rural landscapes and exist in areas that are sparsely populated and lack formalized fire protection. In some cases, lands that are designated as wildland-urban interface are comprised of significant portions of unprotected lands. Currently, there has been little in the way of research completed that pertains to the overall amount of land that is designated as unprotected. Additionally, definitional obfuscation between land management agencies, researchers, and land holders lead to confusion about the overall level of formal fire protection landscapes do or do not have. Research surrounding the social characteristics of human populations that inhabit unprotected lands is even more limited than the geospatial attributes of those landscapes. This research is a case study of one community, located in Washington State, that is located on unprotected lands. Semi-structured, in-depth interviews were conducted with 32 participants who live in the study area. Participants were asked questions to assess their level of knowledge about unprotected lands and to determine their preferences regarding the introduction of formalized fire protection. Over the course of the field work, data was also gathered pertaining to participants' capacity to adapt to wildfire and the social characteristics that are present within the community that could impact their ability to 'live with wildfire.' We discovered that a large proportion of participants were unaware that they had no formalized fire protection and displayed significant lack of knowledge about unprotected lands. Those participants, however, shared social characteristics with the participants that were aware of their level of fire protection that promote a sense of collective self-sufficiency and a rejection of outside interference. Those participants who were aware of the unprotected lands situation did profess a need for some type of additional fire protection for their community, but in general, participants favored managing wildfire risk on their own. Highlights: Some US residents live in areas without formal fire protection and are unaware of it. Unprotected lands present a challenge for inhabitants, policy makers, and firefighters. Social characteristics of communities should be considered in management decisions. Some community types are more capable of self-managing wildfire risk.